THE USAGE OF GRAPHICAL PASSWORD AS A REPLACEMENT TO THE ALPHANUMERICAL PASSWORD - Hartanto, Budi; Santoso, Bagus; Welly, Siauw (Institute of Research and Community Outreach - Petra Christian University, 2006)
Alphanumerical password is the password scheme that obligates the users to enter characters as their password. In spite of its popularity, alphanumerical password usually can be cracked easily when it is used by novice users. Since these users usually type their password slowly, unauthorized person can get the password easily by observing the movement of the users' finger as they entering the password. A graphical password is proposed to replace the alphanumerical password. From the experiment it can be shown that none of users graphical password can be cracked, meanwhile 80% of the users' alphanumerical password can be cracked by the researcher. However in average, users need only 4.68 seconds to enter the password in alphanumerical password scheme, meanwhile in graphical password scheme it takes about 39.06 seconds. Hence password entry in the graphical password scheme needs about 8 times longer than in alphanumerical password. Based on this fact, the graphical password may still be considered to be used in applications that do not need a rapid password entry and the system security is becoming the main issue.